A study of the usefulness of inspection of radiology reports in the emergency room. Issue 1 (10th December 2020) - Koyama, Toru; Yoshiike, Shouichi; Suganuma, Kazuki; Shiroto, Kosuke; Miyauchi, Naoto; Shinchu, Sayaka; Aoki, Yoshihiro
Abstract : Aim: The aim of this study was to better understand the usefulness of retrospective inspection of radiology reports of CT (computed tomography) or MRI (magnetic resonance imaging) by emergency doctors in the emergency room. Methods: Between April 2018 and March 2019, patients who went home after CT or MRI who needed to change their treatment plans and subsequent corresponding procedures after inspection of radiology reports by emergency doctors were reviewed. Results: Among 7, 661 CT or MRIs performed on 5, 917 patients, there were 131 patients (133 CT or MRI or 1.7% among 7, 661 examinations) who required a change in their treatment plans after inspection of radiology reports. Of the 133 CT or MRI performed, there were 51 (38.3% among 133 CT or MRI, 0.7% among 7, 661 examinations) CT or MRI performed, which indicated findings to suspect a tumor (11.8% in the head, 41.2% in the chest, 35.3% in the abdomen, and 11.8% in others). With the need to make important changes in treatment plans, making appointments for outpatient clinics was necessary for 52 CT or MRI findings, and requiring the patients to return to the clinic or be admitted was necessary for 9 (totally 61; 0.8% among 7, 661 examinations). Conclusion: Data from this study suggest that inspection of radiology reports of CT or MRI by emergency doctors after patients went home is useful in finding characteristics suggestive of tumors in 0.7% of all radiology reports and is necessary to identify important changes that should be made in treatment plans in 0.8% of all radiology reports. Abstract : Data from this study suggest that inspection of radiology reports of CT or MRI by emergency doctors after patients went home is useful in finding characteristics suggestive of tumors in 0.7% of all radiology reports and is necessary to identify important changes that should be made in treatment plans in 0.8% of all radiology reports.